Spatiotemporal dynamics of SETD5-containing NCoR–HDAC3 complex determines enhancer activation for adipogenesis - Yoshihiro Matsumura (Nature Portfolio, 2021)
How enhancers transition from a hypoacetylated primed state to a hyperacetylated-active state in response to differentiation stimuli is incompletely understood. Here the authors show that SETD5 forms a complex with NCoR-HDAC3 co-repressor to prevent histone acetylation of master adipogenic gene enhancers, while SETD5 degradation triggers enhancer hyperacetylation and transition to active state.